Taxonomic revision of the genus Psoricoptera Stainton, 1854 (Lepidoptera: Gelechiidae: Gelechiinae) from China, with descriptions of three new species - Zheng, Meiling; Li, Houhun (Zootaxa, 2021)
The Chinese fauna of Psoricoptera Stainton, 1854 included two described species prior to this study. In the present paper we describe three new species: P. curva sp. nov., P. minutignatha sp. nov. and P. proximikawabei sp. nov. P. speciosella Teich, 1893 is recorded from China for the first time. The total number of Psoricoptera species in China is brought to six. The female of P. latignathosa is described for the first time. Photographs of adults and genitalia are provided, along with a key to the Chinese species. A Neighbor-Joining (NJ) tree is provided for species identification and association of the sexes.